Achatina fulica na zona rural de Maringá, Paraná: relações ambientais - Eduvirgem, Renan Valério; Ferreira, Maria Eugênia Moreira Costa (Revista Brasileira de Geografia Física, 2020)
O objetivo da pesquisa é avaliar a distribuição espacial do molusco Achatina fulica, espécie exótica, na zona rural do município. Para caracterizar e explicar a ocorrência positiva da espécie foram avaliados os seguintes elementos: localização em coordenada, temperatura, umidade, insolação, altitude e avaliação da arborização/cobertura vegetal. Em campo, foram detectados 40 propriedades rurais que possuem a espécie exótica, dispersa nas proximidades das residências, barracões, e não em meio às culturas temporárias. As entrevistas indicaram que a maior parte dos entrevistados aplicam os procedimentos de contato manual de forma adequada, cujo propósito é evitar a contaminação pelo helminto Angiostrongylus sp. Entretanto, o risco não está isento, pois há pessoas que têm contato com a espécie sem proteção nas mãos e, em mais de 50% das residências há roedores (ratos), que são hospedeiros definitivos do verme. Achatina fulica in rural zone of Maringá, Paraná: environmental relations A B S T R A C T The objectives of this research are: 1) map the current spatial distribution of the mollusc Achatina fulica in the rural zone and its interaction with the environmental conditions in which they are found in the rural area of the municipality of Maringá, Paraná; 2) evaluate the potential risks to human health through the questionnaires used during the interviews; 3) assess whether the population is vulnerable to contamination by the giant African snail. The methodological procedures were established in the following steps: determining the sample size; distribution of points using the grid to not influence the choice of locations to be interviewed; authorization from the ethics board; field interviews; collections of variables in the field to relate to the snail; organize and tabulate the results; generate cartographic products; promote statistical analysis. 40 rural properties were detected that have the exotic species, dispersed in the vicinity of the residences, sheds, and not among the temporary cultures. The interviews indicated that most of the interviewees apply the procedures of manual contact in an appropriate way, whose purpose is to avoid contamination by the helminth Angiostrongylus sp. The risk is not exempt, as there are people with contact with the species without protection in their hands and, in more than 50% of the residences there are rodents (rats) - according to information raised with the residents. The snail was found at intermediate altitudes with declines of up to 12%. It was concluded that the rural area has favorable environmental conditions for the survival and reproduction of Achatina fulica, however, snails are found in specific places, thus increasing the chances of success in controlling the species. Keywords: Biogeography, environmental analysis, geographic distribution, exotic Species.